2018
DOI: 10.1103/physreva.97.042702
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and theoretical electron-scattering cross-section data for dichloromethane

Abstract: We report on a combination of experimental and theoretical investigations into the elastic differential cross sections (DCS) and integral cross sections (ICS) for electron interactions with dichloromethane, CH 2 Cl 2 , in the incident electron energy over the 7.0-30 eV range. Elastic electron scattering cross section calculations have been performed within the framework of the Schwinger multichannel method implemented with pseudopotentials (SMCPP), and the independent atom model with screening corrected additi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
22
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(31 citation statements)
references
References 42 publications
8
22
1
Order By: Relevance
“…At 5eV, the SMC data of Natalense et al [21,22] also agree well with our data. At 10eV, our experimental DCS show very good agreement with both the present MCOP results and the SMCPP data of Krupa et al [24]. Particularly, a shoulder at near 25°and a shallow minimum at near 110°seen in our experimental data are reproduced by both calculations.…”
Section: Resultssupporting
confidence: 91%
See 4 more Smart Citations
“…At 5eV, the SMC data of Natalense et al [21,22] also agree well with our data. At 10eV, our experimental DCS show very good agreement with both the present MCOP results and the SMCPP data of Krupa et al [24]. Particularly, a shoulder at near 25°and a shallow minimum at near 110°seen in our experimental data are reproduced by both calculations.…”
Section: Resultssupporting
confidence: 91%
“…The experimental DCS, ICS, and MTCS for elastic electron scattering by CH 2 Cl 2 obtained in CSUF and UFSCar are listed in tables 1 and 2, respectively. A comparison of the experimental DCS with our theoretical results, calculated at MCOP and IAM levels of approximation, and with the calculated and measured data of Krupa et al [24] is shown in figures 1-3. In the 5-30eV E range, the theoretical results of Natalense et al [21,22] using the SMC approach without the inclusion of polarization effects are also shown.…”
Section: Resultsmentioning
confidence: 62%
See 3 more Smart Citations